2021
DOI: 10.1177/03635465211059811
|View full text |Cite
|
Sign up to set email alerts
|

Joint Line Obliquity Does Not Affect the Outcomes of Opening Wedge High Tibial Osteotomy at an Average 10-Year Follow-up

Abstract: Background: A significant number of high tibial osteotomies (HTOs) result in an overcorrected tibia and subsequent excessive lateral joint line obliquity (JLO). The correlation between excessive JLO and poor outcomes is controversial. Purpose: To evaluate the prognostic factors (including a pathological postoperative JLO) related with the outcomes of opening wedge HTO at 10 years of follow-up. Study Design: Case series; Level of evidence, 4. Methods: All patients undergoing HTO between 2004 and 2017 for medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…This reduces shearing forces over the joint line as well as altered load stresses over the lateral tibial plateau. 3,15,34,38 However, preservation of joint line obliquity remains controversial, with some studies suggesting that it does not affect clinical outcomes owing to compensatory mechanisms 4,10,31 and with others reporting the opposite contrary. 1,34 There is evidence to suggest that type III fractures may occur because of abnormal loading over the lateral tibia, especially once patients commence weightbearing activities.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces shearing forces over the joint line as well as altered load stresses over the lateral tibial plateau. 3,15,34,38 However, preservation of joint line obliquity remains controversial, with some studies suggesting that it does not affect clinical outcomes owing to compensatory mechanisms 4,10,31 and with others reporting the opposite contrary. 1,34 There is evidence to suggest that type III fractures may occur because of abnormal loading over the lateral tibia, especially once patients commence weightbearing activities.…”
Section: Discussionmentioning
confidence: 99%
“…The medial proximal tibial angle (MPTA) was defined as the angle between the tibial mechanical axis and articular surface of the proximal tibia. 29 , 33 , 40 The tibial slope was measured as the angle between the line perpendicular to the middiaphysis of the tibia and the line depicting the posterior inclination of the tibial plateau in the lateral view. 23 The medial joint space width was measured from the center of the MFC to the center of the MTP on the Rosenberg view, as described in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“…It also has been suggested that the IVHTO technique may be a good option for larger corrections. 9 Typically, larger corrections are achieved using either a single osteotomy in the coronal plane, accepting some postoperative joint line obliquity, or a double-level osteotomy, 11,12 which is more complex. The benefits of an IVHTO over these 2 options have yet to be proved, and indeed the results presented by Hayashi et al 10 show that the postoperative medial proximal tibial angle, a measure of joint line obliquity, was similar in their 2 groups: 94.5 AE 2.9 in the IVHTO group and 95.6 AE 2.7 in the CWHTO group.…”
Section: See Related Article On Page 1956mentioning
confidence: 99%